Pengaruh Ukuran Butir Terhadap Porositas dan Permeabilitas pada Batupasir - Nurwidyanto, M. Irham; Yustiana, Meida; Widada, Sugeng (BERKALA FISIKA, 2006)
It has been done a research to know the influence of grain size to permeabiality and porosity on sandstones from Ngrayong Formation, Ledok Formation, Kerek Formation and Selorejo Formation. The Permeability is measured by RUSKA Permeameter Gas, while the porosity is measured by  Porosimeter Gas A-9756 series. The grain size is then determined  using grain size analysis method. After the calculation, the grain size is attributed to permeability and porosity of sandstones with the analysis regresi method. Results obtained indicate that the influence of grain size significant at six sandstones. Based on the statistic calculation it has been obtained the relation  with Linear regression  equation Log k= -5.7 Log d + 15 with r2=0.7, for the grain size to permeability and = -1.9x102d +75 with  r2=0.7,  for the relation of grain size to porosity.   Key Word: sandstone, grain size, porosity, permeability